Detection of nerve structures during peripheral nerve blockade in pigs model - Ilvana Hasanbegovic; Eldan Kapur; Amela Kulenovic; Asija Gojacic; Amela Dzubur; Jasmin Musanovic; Esad Pepic (Archives of Global Professionals, 2013)
Objective: In recent years regional anesthesia has gained great popularity. However, like any other medical procedure, the regional anesthesia carries certain risk of unintended intraneural injection and consequential neurological complications. Studies in animals have suggested that intraneural application of local anesthetics may cause mechanical injury. Previous studies, however, have used small animal models and clinically irrelevant injection speed or equipment. In this study we used equipment and injection methods in common clinical use to study the consequences and pressure dynamics of intraneural injection. Our hypothesis is that an intraneural injection is heralded by higher injection pressure and leads to neurologic impairment in pigs. Materials and Methods: Ten pigs of mixed breed (21-26 kg, 4-6 months old) were studied. After general anesthesia, the sciatic nerves (n = 20) were exposed bilaterally. Under direct vision, a 25-gauge insulated nerve block needle was placed either intraneurally (n = 10) or perineurally (n = 10), and 4 ml of preservative-free lidocaine 2% was injected using an automated infusion pump (15 ml/min). Injection pressure data were acquired using an in-line manometer coupled to a computer via an analog-to-digital conversion board. After injection, the animals were awakened and subjected to serial neurologic examinations during next 7 days. Results: All perineural injections resulted in injection pressures below 40 kPa. In contrast, intraneural injections resulted in significantly higher peak pressures (P < 0.01). In seven (70%) intraneural injections, the injections pressures were over 140 kPa (140-350 kPa). Neurologic function returned to baseline within 24 hours in all sciatic nerve receiving perineural injections. In contrast, residual neurologic impairment was present in seven sciatic nerves after intraneural injection and was associated with injection pressures >140 k Pa. Conclusion: High injection pressure (>140 kPa) predicts intraneural injection and consequential neurologic deficit. As long as the injection pressure is low, injection into poorly compliant tissue can be avoided and neurological complication can be prevented.